Is resale anxiety an obstacle to electric vehicle adoption? Results from a survey experiment in Switzerland - Gracia Brückmann; Michael Wicki; Thomas Bernauer (Environmental Research Letters, 2021)
Electrification of private motorised transport is one of the most effective pathways to net-zero carbon emissions in the road transport sector. However, adoption rates of battery-electric vehicles (BEVs) are still relatively low in most advanced industrialised countries. One of the most widely discussed but so far understudied potential obstacles to BEV adoption is resale anxiety. It refers to the fear of comparatively low expected resale values of BEVs, resulting, among other reasons, from expectations concerning rapid progress in battery technology. However, based on three survey-embedded vignette experiments in Switzerland ( N = 3901 in total), we find the opposite of resale anxiety: a higher expected resale value of BEVs compared to conventional cars. Our findings suggest that regulatory policy and social norm signals in this area are gaining ground, boding well for consumer acceptance of BEVs in the coming years.